Assessment of the role of school health nurses/school health supervisors in the prevention and control of communicable diseases in primary schools in Derna, Libya - Arhaim, Saria M.; Elzahaf, Raga A. (International Journal Of Community Medicine And Public Health, 2016)
Background: The nurse’s role is primarily a manager of the health services program, she provide the leadership or play a supporting role in prevention and control of communicable diseases in schools. She is the first point of contact in the school on most health services. The aim of the present work was to assess of the role of the school health nurse/ school health supervisor in the prevention and control of communicable diseases in primary schools in Derna, Libya. Methods: A cross-sectional study design was used. The study was conducted in the primary schools of Derna city, Libya. The study included all nurses (50 nurses) working in 26 primary schools. Data was collected used a predesigned and structured questionnaire to collect the personal characteristics and specially constructed observational checklist was prepared to assess the role of SHNs/SHSs regarding prevention and control of communicable diseases. Results: About two thirds of the studied sample aged 30 to <40 years (62.0%). Majority of them (96.0%) were responsible for one school, with workload of 200 to >410 students. About three quarters of them received training courses in school health. 58.0% of the studied sample adequately performed their activities regarding prevention and control of communicable diseases. Conclusions: The study recommends increase awareness of school principals on the school-nursing role, especially in issues related to prevention and control of communicable diseases.